THE EFFECT OF STUDENT TEAMS-ACHIEVEMENT DIVISION (STAD) TECHNIQUE TOWARD STUDENTS’ SPEAKING SKILL AND CLASS PARTICIPATION - Ildi Kurniawan; Mukhaiyar .; Yenni Rozimela (Journal of English Education and Teaching, 2017)
This quasi-experimental research was aimed to find out the effect of STAD technique toward students’ speaking skill and class participation at grade XI of SMAN 5 Kota Bengkulu in academic year of 2011/2012. The population of this research was the students at grade XI of SMAN 5 Kota Bengkulu in academic year of 2010/2011 that consisted of 168 students. The sample of this research was IPA 4 which comprised 27 students and IPA 5 which comprised 27 students and the two classes were cluster randomly selected as a research sample. The data were collected through speaking test and observation sheet of class participation. The data were then analyzed by using t-test and analysis of variances.  The findings of this research showed that (1) the students who were taught by using STAD technique gave significant effect toward their speaking skill achievement. (2) The students who were taught by using STAD technique gave significant effect toward their class participation. (3) The students who were taught by using STAD technique gave significant effect toward students’ speaking skill and class participation. Thus, it can be concluded that STAD technique gave significant effect toward students’ speaking skill and class participation at grade XI of SMAN 5 Kota Bengkulu in academic year of 2011/2012.